Policy Networks and Forest Resource Management in Ghana - Teye, J.K. (Department of Geography, University of Ghana, 2010)
This paper employs a policy network model to explore the formal and informal interactions and structures which characterize forest management in Ghana. A comprehensive analysis of primary and secondary data reveals that forest management in Ghana has historically been influenced by complex relations of power and networks between local communities and the Forest Services Division. While resource constraints have often been used by state forestry officials to justify inability to control deforestation, the paper concludes that the problem is also compounded by the pervasiveness of patronage relationships between and among forestry officials, timber contractors, illegal chainsaw operators and farmers. Based on these findings, the paper recommends that strengthening of state forestry organizations must be accompanied by greater transparency on the part of forestry officials. It is also recommended that the interests of people in forest fringe communities must be carefully considered whenever a forest policy is being designed
Keywords: Forest management, networks, power relations, Ghana